ASHRAE greenguide : design, construction, and operation of sustainable buildings. (ASHRAE, 2018)
"Provides information on green-building design. Concerned with sustainable, high-performance projects"-- Provided by publisher
Keywords: Sustainable buildings -- Design and construction.; Sustainable buildings -- United States -- Design and construction.; Sustainable architecture.; Buildings -- Environmental engineering.; Sustainable construction.; elektronické knihy; electronic books